Personalized Medicine: Futuristic Predictive Nanomedicines for Diagnosis and Therapeutics - Chavda, Vivek P (Genes Review, 2016)
The concept of personalized medicine has got its credential due to the development of molecular techniques. It involves right drug & dose, right patient and with right time administration of a medication. By averting the knowledge of gene sequence and their functions, biomedical researches are diversified towards inter-individual variations that are expected to become an eminent part of treatment planning in terms of efficacy and toxic side effects of drugs. The clairvoyance of the future health care adjudicate a system in which patient care is consistently belay by captivating information on the individual patient’s genomes and their downstream products. By combining the credentials of various disciplines such as life sciences, mathematics, physics, chemistry, and information and communication technology ameliorated this concept. These have been well addressed by the so called ‘-omics’ technology. However, assimilation of genomic data to its risk-benefit analyses and the adaptability of the patient population with certain ethical issue becomes one pillar for this and the view of the pharmaceutical industry towards this discipline.